2015
DOI: 10.1155/2015/351698
|View full text |Cite
|
Sign up to set email alerts
|

L-Lactate Protects Skin Fibroblasts against Aging-Associated Mitochondrial DysfunctionviaMitohormesis

Abstract: A moderate elevation of reactive oxygen species (ROS) production and a mild inhibition of mitochondrial respiratory chain have been associated with a health promotion and a lifespan extension in several animal models of aging. Here, we tested whether this phenomenon called mitohormesis could be mediated by L-lactate. The treatment with 5 mM L-lactate significantly increased H2O2 production and slightly inhibited the respiration in cultured skin fibroblasts and in isolated mitochondria. The L-lactate exposure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 49 publications
4
30
0
Order By: Relevance
“…Interestingly, the mitochondria not only phenotypically changed with LA treatment, but there was also an increase in MTG incorporation measured (Supp Fig 1l). Since lactic acid and TCM induced an oxidative and energetic stress, we also performed a viability assay (Supp Fig 1m) but no differences were observed consistent with previous studies (Zelenka et al, 2015). In summary these data indicate that tumor-derived lactic acid is sufficient to recapitulate mitochondrial changes and activation signatures induced by TCM in FRCs of TDLNs.…”
Section: Lactate Induces Mitochondrial and Activation Reprogramming Isupporting
confidence: 86%
“…Interestingly, the mitochondria not only phenotypically changed with LA treatment, but there was also an increase in MTG incorporation measured (Supp Fig 1l). Since lactic acid and TCM induced an oxidative and energetic stress, we also performed a viability assay (Supp Fig 1m) but no differences were observed consistent with previous studies (Zelenka et al, 2015). In summary these data indicate that tumor-derived lactic acid is sufficient to recapitulate mitochondrial changes and activation signatures induced by TCM in FRCs of TDLNs.…”
Section: Lactate Induces Mitochondrial and Activation Reprogramming Isupporting
confidence: 86%
“…The effectiveness of a pre-treatment as a potential protective mechanism suggests the induction of a protective response or hormesis that would reduce the impact of lethal stress later on 18,19,31 . Work by others has shown that lactate promotes ROS induction 32,33 , suggesting that this mechanism could mediate the observations reported here.…”
Section: Lactate Reduces Cell Death Through Ros Signalingsupporting
confidence: 78%
“…45 Metabolic alterations coupled with enhanced stress tolerance likely contribute to the delayed senescence and lifespan extension of rictordeficient keratinocytes, in keeping with similar reports on fibroblasts. 46 As hyperactive DNA replication forks promote senescence, the spontaneous immortalization of E-RiKO keratinocytes may result from senescence bypass favored by metabolic reprogramming, mitohormesis and reduced proliferation rates. As sustained exposure of E-RiKO keratinocytes to NAC enhances BrdU uptake and favors senescence in the absence of exogenous stressors, ROS elevations may contribute to the proliferative and senescence phenotypes of mutant cells.…”
Section: Discussionmentioning
confidence: 99%